Argentine Fraternity and Liberal-Libertarian Balkanization - PROTO GUTIERREZ, Fernando (Utopía y Praxis Latinoamericana, 2025)
The present study proposes a relational meta-theoretical articulation of homeomorphic equivalence designed from a formalized reading according to the hermeneutic method of Panikkar (1990) and Estermann (2021) in order to understand the “estar” (Scannone: 1990) and “Ubuntu” (Ramose: 2002), from the perspective of the “nosotos-estamos”. These categories are applied to the horizon of interpretation of the Argentinean debt crisis and balkanization, which occurred after COVID-19 and its consequences in the destructuring of the fraternal bond, as a condition for the realisation of social-community justice.